Tradisi Mappamula Ase Baru pada Awal Panen Padi dalam Masyarakat Bugis di Desa Rarongkeu Kecamatan Lantari Jaya Kabupaten Bombana - Salma Yuliana Tou; Nurtikawati; Shinta Arjunita Saputri (LISANI: Jurnal Kelisanan, Sastra, dan Budaya, 2023)
The Mappamula Ase Baru tradition is a tradition of the Bugis people which is carried out when entering the beginning of the rice harvest. This study aims to 1) find out the process of implementing the Mappamula Ase Baru Tradition in the Bugis community in Rarongkeu Village, Lantari Jaya District, Bombana Regency; 2) analyze the function of the Mappamula Ase Baru Tradition in the Bugis community in Rarongkeu Village, Lantari Jaya District, Bombana Regency. In this study, Bronislaw Malinowski's Functionalism theory was used. The type of research was descriptive qualitative, with data collection techniques carried out by observation, interviews and documentation and then analyzed by data reduction, data presentation, and data verification. The results of this study indicate that the process of the Mappamula Ase Baru tradition consists of three stages, namely the preparatory stage which consists of determining the time and providing offerings, implementation, namely where the new Mappamula Ase tradition will be carried out on the community's agricultural land and led by sandro (shaman) and the stage the third, namely the final stage, is to bring back to the house a few stalks of rice that have been taken and placed in the center or center pillar of the house. The Mappamula Ase Baru tradition has a function that is believed by the Bugis community, namely as an identity and a function of belief.